Wastes in the ocean v.5 deep-sea waste disposal. - Kester, Dana R.; Burt, Wayne V.; Capuzzo, Judith M.; Park, P. Kilho; Ketchum, Bostwick H.; Duedall, Iver W. (John Wiley & Sons, Inc., 1985)
A Wiley-Interscience publication. Wastes in the ocean ; v. 5 Environmental science and technology